Volume 3: Materials and Joining; Pipeline Automation and Measurement; Risk and Reliability, Parts a and B 2006
DOI: 10.1115/ipc2006-10350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grade on Ductile Fracture Arrest Criteria for Gas Pipelines

Abstract: Several different criteria have been proposed over the years to predict the minimum toughness for arrest of an axial propagating crack for natural gas pipelines. The initial ones were empirically based. The Battelle Two-Curve Method (TCM) was subsequently developed and was somewhat less empirical. The TCM is still used frequently today. Nevertheless, all of these criteria use the Charpy energy as a measure of the material’s ductile fracture resistance. As higher-grade steels have been developed, it has been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For modern higher grade steels, if the predicted CVN value is greater than ~95 J [57], then the CVN value should be corrected using a certain correction factor to match the results of full-scale burst tests [58,59]. The Australian Standard (AS 2885.1), states that the predicted toughness should be multiplied by a factor of at least 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…For modern higher grade steels, if the predicted CVN value is greater than ~95 J [57], then the CVN value should be corrected using a certain correction factor to match the results of full-scale burst tests [58,59]. The Australian Standard (AS 2885.1), states that the predicted toughness should be multiplied by a factor of at least 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wilkowski et al [55] showed that the pipeline grade has a significant effect on the correlation between CVN and DWTT energies. The slope of the linear function continues to decrease from 2.94 ($3.00 as obtained in Eq.…”
Section: Early Dwtt Methods At Battellementioning
confidence: 98%
“…On this basis, they obtained the so-called Wilkowski 1977 prediction of CVN energy from the standard DWTT tests: In order to apply this nonlinear DWTT-CVN relationship to pipeline grades up to X70, a statistical factor 1.3 was inserted before (E/A) DWTT in the square brackets of Eq. (11), which leads to another correlation equation called the Wilkowski 2000 prediction of the CVN energy from the standard DWTT tests [55]. Note that these correlations between DWTT and CVN energies are not corrections to relate actual to predicted arrest CVN toughness.…”
Section: Wilkowski Dwtt Correlationsmentioning
confidence: 97%
See 2 more Smart Citations